Endothelial HSPA12B Exerts Protection Against Sepsis-Induced Severe Cardiomyopathy via Suppression of Adhesion Molecule Expression by miR-126 - Zhang, Xia; Wang, Xiaohui; Fan, Min; Tu, Fei; Yang, Kun; Ha, Tuanzhu; Liu, Li; Kalbfleisch, John; Williams, David; Li, Chuanfu (Frontiers in Immunology, 2020)
Heat shock protein A12B (HSPA12B) is predominately expressed in endothelial cells (ECs) and has been reported to protect against cardiac dysfunction from endotoxemia or myocardial infarction. This study investigated the mechanisms by which endothelial HSPA12B protects polymicrobial sepsis induced cardiomyopathy. Wild type (WT) and endothelial HSPA12B knockout (HSPA12B-/-) mice were subjected to polymicrobial sepsis induced by cecal ligation and puncture (CLP). CLP sepsis accelerated mortality and caused severe cardiac dysfunction in HSPA12B-/- mice compared with WT septic mice. The levels of adhesion molecules and the infiltrated immune cells in the myocardium of HSPA12B-/- septic mice were markedly greater than in WT septic mice. The levels of miR-126, which targets adhesion molecules, in serum exosomes from HSPA12B-/- septic mice were significantly lower than in WT septic mice. Transfection of ECs with adenovirus expressing HSPA12B significantly increased miR-126 levels. Increased miR-126 levels in ECs prevented LPS-stimulated expression of adhesion molecules. In vivo delivery of miR-126 carried by exosomes into the myocardium of HSPA12B-/- mice significantly attenuated CLP sepsis increased levels of adhesion molecules and improved CLP sepsis induced cardiac dysfunction. The data suggests that HSPA12B protects against sepsis induced severe cardiomyopathy via regulating miR-126 expression which targets adhesion molecules, thus decreases the accumulation of immune cells in the myocardium.